The voice characterisation checklist: psychometric properties of a brief clinical assessment of voices as social agents - Edwards, Clementine J.; Owrid, Oliver; Miller, Lucy; Jafari, Hassan; Emsley, Richard; Rus-Calafell, Mar; Craig, Thomas K. J.; Clancy, Moya; McLeod, Hamish; Fornells-Ambrojo, Miriam; McDonnell, Jeffrey; Montague, Alice; et al. (Frontiers in Psychiatry, 2023)
Aim There is growing interest in tailoring psychological interventions for distressing voices and a need for reliable tools to assess phenomenological features which might influence treatment response. This study examines the reliability and internal consistency of the Voice Characterisation Checklist (VoCC), a novel 10-item tool which assesses degree of voice characterisation, identified as relevant to a new wave of relational approaches. Methods The sample comprised participants experiencing distressing voices, recruited at baseline on the AVATAR2 trial between January 2021 and July 2022 (n = 170). Inter-rater reliability (IRR) and internal consistency analyses (Cronbach’s alpha) were conducted. Results The majority of participants reported some degree of voice personification (94%) with high endorsement of voices as distinct auditory experiences (87%) with basic attributes of gender and age (82%). While most identified a voice intention (75%) and personality (76%), attribution of mental states (35%) to the voice (‘What are they thinking?’) and a known historical relationship (36%) were less common. The internal consistency of the VoCC was acceptable (10 items, α = 0.71). IRR analysis indicated acceptable to excellent reliability at the item-level for 9/10 items and moderate agreement between raters’ global (binary) classification of more vs. less highly characterised voices, κ = 0.549 (95% CI, 0.240–0.859), p < 0.05. Conclusion The VoCC is a reliable and internally consistent tool for assessing voice characterisation and will be used to test whether voice characterisation moderates treatment outcome to AVATAR therapy. There is potential wider utility within clinical trials of other relational therapies as well as routine clinical practice.